Educational Networks 2.1: Social media, collaborative environments and teaching-learning processes - Levis, Diego (Revista de universidad y sociedad del conocimiento, 2011)
The Redes Educativas 2.1 (Educational Networks 2.1) project attempts to investigate the potential of social media and collaborative environments on the Internet for teaching-learning processes. To that end, we used a Web 2.0 application for social network creation on face-to-face courses and on blended-learning teacher training courses. The application was configured in accordance with the pedagogical needs of every course included in the project. A space restricted to course participants was created, and students of the same subject on several courses and/or years were incorporated, as were the lecturers. Educational networks, as collaborative environments, do not refer to computers, cables, satellites or software. Rather, they describe the participants in a specific educational experience who are connected via an electronic system that facilitates interaction between them. The versatility of educational networks allows various teaching-learning methods to be combined in a single study space. Alongside teaching practices that are more traditional, it is possible to generate contexts that include collaborative and cooperative practices based on horizontality. Finally, the meaning of educational networks is linked to the pedagogical project into which each experience falls. Technology in itself does not innovate; rather, it is the social appropriation of technology — educational in this instance — that leads to change.